2010
DOI: 10.1002/pits.20517
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of personal experiences: Effects on students' learning and behavioral intentions toward peers with Attention‐Deficit/Hyperactivity Disorder

Abstract: High-school students were shown an educational video designed to dispel 12 common myths regarding Attention-Deficit/Hyperactivity Disorder (ADHD) by describing each myth and then presenting accurate information. The experimental group viewed a video that was supplemented by the speaker acknowledging that he had ADHD and providing descriptions of personal experiences (DPE) designed to highlight the injury caused by 6 of the 12 common myths. Findings suggest that including the DPE may have enhanced learning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…One study (Saecker et al . ) considered the best way to present educational information regarding ADHD to peers, indicating that videos including those with the disorder talking about the personal impact may be a particularly powerful way to transmit related information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study (Saecker et al . ) considered the best way to present educational information regarding ADHD to peers, indicating that videos including those with the disorder talking about the personal impact may be a particularly powerful way to transmit related information.…”
Section: Resultsmentioning
confidence: 99%
“…One study recorded data on whether participants themselves had ADHD or another disability (Saecker et al . ). One teacher study reported that all participants had prior experience of teaching at least one student with ADHD (Ohan et al .…”
Section: Discussionmentioning
confidence: 97%